General Principles in Electrospray Mass Spectrometry: A New Technique in Mass Spectral Analysis - Djulia Onggo; Daud K. Walanda; Robert C. Burns; Geoffrey A. Lawrance; Ellak I. von Nagy-Felsobuki (Institut Teknologi Bandung, 1998)
Electrospray mass spectrometry analyzes ions which have been generated in the gas-phase from electrically charged droplets obtained by nebulizing a solution. While the generation of an aerosol by electrospray was published by Zeleny in 1917, it was not until approximately some seven decades later when it was successfully interfaced to a mass spectrometer, thereby extending significantly the use of mass spectrometry in inorganic, biological and trace element research. The mechanism of ion generation by electrospray is still not definitively understood nor is the limitation of its linear dynamic range with respect to analyte concentration. This review will describe the general principles underlying this new technique.